Effects of Type 1 Insulin-Like Growth Factor Receptor Silencing in a Human Adrenocortical Cell Line - Ribeiro, T. C.; Jorge, A. A.; Montenegro, L. R.; Almeida, M. Q.; Ferraz-de-Souza, B.; Nishi, M. Y.; Mendonca, B. B.; Latronico, A. C. (Hormone and Metabolic Research, 2016)
Type 1 insulin-like growth factor receptor (IGF-1R) is overexpressed in a variety of human cancers, including adrenocortical tumors. The aim of the work was to investigate the effects of IGF-1R downregulation in a human adrenocortical cell line by small interfering RNA (siRNA). The human adrenocortical tumor cell line NCI H295R was transfected with 2 specific IGF1R siRNAs (# 1 and # 2) and compared with untreated cells and a negative control siRNA. IGF1R expression was determined by quantitative reverse-transcription PCR (qRTPCR) and Western blot. The effects of IGF-1R downregulation on cell proliferation and apoptosis were assessed. IGF-1R levels were significantly decreased in cells treated with IGF-1R siRNA # 1 or # 2. Relative expression of IGF1R mRNA decreased approximately 50% and Western blot analysis revealed a 30% of reduction in IGF-1R protein. Downregulation of this gene resulted in 40% reduction in cell growth in vitro and 45% increase in apoptosis using siRNA # 2. These findings demonstrate that decreasing IGF-1R mRNA and protein expression in NCI H295R cells can partially inhibit adrenal tumor cell growth in vitro. Targeting IGF1R is a promising therapy for pediatric malignant adrenocortical tumor and can still be an option for adult adrenocortical cancer based on personalized genomic tumor profiling.
Keywords: IGF system; IGF-1R; siRNA; adrenocortical tumors